Cholecystitis in Pregnancy - Brian M. Casey; Susan M. Cox (Hindawi Limited, 1996)
Biliary tract disease is a relatively uncommon, heterogenous disease in pregnancy. Specifically, acute cholecystitis can be especially difficult to recognize in pregnancy. However, once diagnosed, the initial management plan should be conservative and include antibiotic therapy. Subsequent management depends on the gestational age at diagnosis. Surgical therapy, when indicated, should not be delayed and a planned intervention during the second trimester appears to offer a better outcome than surgery performed under emergent conditions.